High-Voltage Direct Current Transmission Systems Based on Silicon Carbide MOSFETs - Li, Zhengyang (Transactions on Computer Science and Intelligent Systems Research, 2024)
High-Voltage Direct Current (HVDC) transmission technology plays a pivotal role in modern power systems due to its capability for efficient long-distance power transmission. Compared to traditional High-Voltage Alternating Current (HVAC) transmission, HVDC systems offer significant advantages in reducing transmission losses, enhancing transmission capacity, and bolstering system stability. In recent years, the use of Silicon Carbide (SiC) materials in power electronic devices has gained widespread attention. Compared to traditional silicon-based MOSFETs, SiC MOSFETs have a higher breakdown electric field, a wider bandgap, and higher thermal conductivity. These characteristics makes them highly promising in high-voltage, high-power applications and considered a significant developmental direction for future high-performance power electronic devices. This paper will initially introduce the material characteristics of SiC, including polymorphism, wide bandgap, and diverse characteristic colors. It will also discuss the structure and main characteristics of SiC MOSFETs, including transfer, output, and breakdown characteristics. Subsequently, it will present the fundamental principles of HVDC systems and the two primary topologies: Line Commutated Converter HVDC and Voltage Source Converters HVDC. Lastly, it will discuss the advantages of SiC MOSFETs over silicon devices in HVDC, along with potential application prospects. The research findings indicate that SiC MOSFETs possess significant application potential and technological advantages in high-voltage direct current transmission, providing theoretical support and a practical foundation for the optimization of future power electronic systems.